Opini Audit Going Concern pada Perusahaan Sektor Transportasi Sebelum dan Ketika Pandemi Covid-19 - Giri, Efraim Ferdinand; Kristianti, Ika Puspita; Kusumanegara, Ratih Ayu (E-Jurnal Akuntansi, 2022)
This study aims to analyze business continuity in terms of liquidity, leverage and KAP turnover in transportation sector companies, especially in 2020 and compared to the previous year, namely 2015-2019. Liquidity is proxied by current ratio, leverage is proxied by debt to assets ratio and turnover of Public Accounting Firm (KAP) is proxied by dummy variable. The sample used is 114 samples of transportation sector companies listed on the Indonesia Stock Exchange during 2015-2020. Data analysis used a logistic regression approach. The results showed that liquidity and leverage level of transportation companies had a negative effect on going-concern audit opinion, while KAP turnover had no effect on going-concern audit opinion. Keywords: Liquidity; Leverage; Going concern; Change of KAP; Covid-19 pandemic